Validation of the Orlando Protocol for endoscopic management of pancreatic fluid collections in the era of lumen‐apposing metal stents. Issue 3 (6th September 2021) - Bang, Ji Young; Wilcox, C. Mel; Arnoletti, Juan Pablo; Peter, Shajan; Christein, John; Navaneethan, Udayakumar; Hawes, Robert; Varadarajulu, Shyam
Abstract : Objectives: Although lumen‐apposing metal stents (LAMS) are being increasingly used in lieu of plastic stents, the clinical approach to endoscopic management of pancreatic fluid collections (PFCs) is poorly standardized. We compared outcomes of approaches over two time intervals, initially using plastic stents and later integrating LAMS. Methods: This was a retrospective, observational, before–after study of prospectively collected data on consecutive patients with symptomatic PFCs managed over two time periods. In the initial period (January 2010–January 2015) endoscopic treatment was undertaken with plastic stents and in the later period (February 2015–August 2020) by integration of LAMS with selective use of plastic stents. The treatment strategy in both periods were tailored to size, extent, type of PFC and stepwise response to intervention. The main outcome was treatment success, defined as resolution of PFC and presenting symptoms at 6‐month follow‐up. Results: A total of 160 patients were treated with plastic stents and 227 patients were treated using an integrated LAMS approach. Treatment success was significantly higher for the integrated approach compared to using only plastic stents (95.6 vs. 89.4%; P  = 0.018), which was confirmed to be predictive of treatment success on multivariable logistic regression analysis (odds ratio 2.7, 95% confidence interval 1.1–6.4; P  = 0.028). Conclusions: A structured approach integrating LAMS with selective use of plastic stents improved treatment success in patients with PFCs compared to an approach using only plastic stents.